A behavior-analytic account of depression and a case report using acceptance-based procedures (Brazilian Journal of Behavioral and Cognitive Therapy, 2003)
Although roughly 6% of the general population is affected by depression at some time during their lifetime, the disorder has been relatively neglected by behavior analysts. The preponderance of research on the etiology and treatment of depression has been conducted by cognitive behavior theorists, biological psychiatrists and psychopharmacologists interested in the biological substrates of depression. These approaches have certainly been useful, but their reliance on cognitive and biological processes and their lack of attention to environment-behavior relations render them unsatisfactory from a behavior-analytic perspective. The purpose of this paper is to provide a behavior-analytic account of depression and to derive, from this account, several possible treatment interventions. In addition, case material is presented to illustrate an acceptancebased approach with a depressed client.